Mapeamento de QTLs para resistência a grãos ardidos causados por diplodia (Stenocarpella Sp.) em milho (Zea Mays L.) - Gutiérrez, Humberto Ignácio (2008)
Diplodia ear rot caused by the fungus Stenocarpella maydis (Berkeley) and Stenocarpella macrospora (Earle) have become one of the most important limiting factors for the production of Corn (Zea mays L.) in Brazil. The fungus can attack the stalks, leaves and the grain causing significant reductions on yield and the overall quality of the grain, since it can produce micotoxinas that are dangerous to livestock. Resistance to ear rot by Stenocarpella sp in corn is quantitative and highly influenced by the environment and even that artificial inoculation techniques are available to screen for the disease the overall cost is very expensive. The objective of this study was the identification of quantitative trait loci (QTL s) associated with ear rot resistance by Stenocarpella sp in one breeding population composed of 141 doublehaploid progenies resulted from the cross among the resistant inbred MONDR1 and the susceptible inbred MONDS1 in testcrosses with the susceptible tester MONDS5. Testcrosses were evaluated at harvest time after artificial inoculation for ear rot at three different locations in the central region of Brazil during the 2005/06 summer season. Thru Composite interval mapping (CIM), a total of three QTL s (LOD>2.5) for ear rot resistance were identified at chromosomes 2, 3 and 5, all together accounting for up 26% of total phenotypic variation for this character. The identification of two QTL s for ear rot resistance coming from the susceptible parent MONDS1 appear to indicate the presence of the phenomena of transgressive segregation. Additionally we were able to identify six double-haploid progenies with high level of resistance to ear rot by Stenocarpella (MDH15, MDH443, MDH95, MDH2, MDH120 e MDH81), being those recommended for their incorporation into the breeding program as new breeding sources for the Central Brazil regions.